2021
DOI: 10.1186/s13027-021-00352-9
|View full text |Cite
|
Sign up to set email alerts
|

Managing head and neck cancer patients during the COVID-19 pandemic: the experience of a tertiary referral center in southern Italy

Abstract: Background The medical community has been deeply involved in fighting the Coronavirus disease 2019 (COVID-19) pandemic and, as a consequence, the care of non-COVID-19 patients has been impacted. However, the treatment of head and neck cancer patients is not deferrable, and an integrated strategy is required. The aim of the current article is to present the experience in the management of head and neck patients during the COVID-19 pandemic at the research hospital “Casa Sollievo della Sofferenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In a COVID-dedicated center, as it was in our experience, modification in the prioritization of surgical procedures, redistribution of human and economic resources, reduction of non-COVID-19-related health care, were just some of the challenges that upset our everyday clinical practice, similarly to other experiences described in Italy (21,22) . All the health providers experienced clinical, managing and ethical issues that are still burdening their everyday activity.…”
Section: Discussionsupporting
confidence: 54%
“…In a COVID-dedicated center, as it was in our experience, modification in the prioritization of surgical procedures, redistribution of human and economic resources, reduction of non-COVID-19-related health care, were just some of the challenges that upset our everyday clinical practice, similarly to other experiences described in Italy (21,22) . All the health providers experienced clinical, managing and ethical issues that are still burdening their everyday activity.…”
Section: Discussionsupporting
confidence: 54%
“…They believe that the COVID-19 pandemic has undoubtedly accelerated the change for future health care systems. 37 Telemedicine, artificial intelligence, and mobile apps will be used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights how much breast cancer diagnosis relies on screening programmes which have suffered badly as a result of the pandemic in England36 and internationally 39. In England, head and neck cancers (HNC) saw a 10.2% (95% CI 7.6% to 12.7%) reduction in diagnosis, while studies in other geographies showed wide differences in the measures’ impact of the pandemic on HNC: a study in Ontario, Canada, found no evidence of a reduction in HNC diagnosis following an initial drop in the 6 weeks following lockdown,40 a clinic in Italy had just a 3.7% reduction in HNC,41 a 14% reduction in Belgium,29 a clinic in California showed a 22% reduction42 and a Cancer Centre in the North of England reported a 33% reduction in HNC cases 43. There is further international evidence of the impact of COVID-19 on interventions down the pathway, with reductions in radical cancer surgeries in two major cancer hubs in England and Italy 44…”
Section: Discussionmentioning
confidence: 99%